A few reflections on managerial authority in temporary employment (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The stimulus for the preparation of the article is the amendment to the Act on the Employment of Temporary Workers, in force since 1 June 2017, which allowed for the widespread use of civil law contracts in temporary employment. This solution raises a number of doubts and interpretation problems, also in the context of managerial authority that in the construction of temporary employment, until the adoption of this amendment, was granted both to the temporary employment agency and the user employer. The main goal of the author is to present managerial authority in temporary employment on three different levels: firstly in case of temporary employees employed on the basis of an employment contract, secondly in case of civil law temporary employment, and thirdly in employee outsourcing, which is the employment option closely linked with the temporary employment and often combined with it. The reflections included in the study show how important the role of managerial authority is in the context of the admissibility of using the atypical form of employment analysed here.